From Organizational Grandiosity to Organizational Silence: The Role of Psychological Capital Depletion and Employee Amygdala Activation in Narcissistic Leadership - Aldi Adi Pratama (Universitas Negeri Padang, 2025)
Narcissistic Leadership (NL) is motivated by a deep need for power and admiration , characterized by organizational grandiosity and excessive self-view. This environment, marked by micromanaging and criticism avoidance, systematically undermines the psychological climate. This study aims to investigate how Organizational Grandiosity under NL creates an atmosphere of chronic threat (reflected by Amygdala Activation), which subsequently depletes employees' positive internal resources (Psychological Capital Depletion), driving them toward Organizational Silence. Utilizing Interpretative Phenomenological Analysis (IPA), the research analyzed in-depth narratives from a small sample (6-10 informants). Key findings confirm an integrative model mediated by dual mechanisms: the biological threat signal of Employee Amygdala Activation and the resource loss of PsyCap Depletion. The convergence of physiological threat and psychological exhaustion compels employees to adopt Defensive Silence as a low-energy, resource-conserving strategy. Organizations must focus on restoring PsyCap and guaranteeing absolute safety for employee voice to mitigate the profound ethical and health costs of NL.